PENENTUAN LOKASI KAWASAN INDUSTRI HASIL TEMBAKAU (KIHT) DI JAWA TENGAH - Ghiyats Alvares Avicenna; Wiwik Budiawan (Program Studi Teknik Industri, Fakultas Teknik, Universitas Diponegoro, 2023)
AbstrakAccording to Government Regulation No. 142/2015 on industrial estates, Minister of Finance Regulation No. 215/PMK.07/2021 on Tobacco Excise Revenue Sharing Funds. There are areas in Central Java that can be included as alternative candidate locations for the Tobacco Products Industrial Estate, but none of these areas have been selected as the Tobacco Products Industrial Estate. This research is to determine the prospective location of the Tobacco Products Industrial Estate. The calculation method uses Analytical Hierarchy Process (AHP). The Analytical Hierarchy Process (AHP) method is used to compare alternatives against each criterion. The analysis process is carried out with an objective approach in order to provide recommendations. The criteria used are aspects of raw materials, production aspects, and sales aspects. As for the alternatives, namely Jepara Regency, Kebumen Regency, Magelang Regency, Purworejo Regency and Wonosobo Regency. The results of the calculation of criteria priorities are the raw material aspect has a priority value of 0.105, the production aspect is 0.637, and the sales aspect is 0.258. While the resulting alternative rating is Jepara Regency 0.309, Kebumen Regency 0.314, Magelang Regency 0.071, Purworejo Regency 0.162, Wonosobo Regency 0.145. Based on the results of data processing and analysis. The result of the selected alternative for the prospective location of KIHT is Kebumen District.Keywords: Location Determination, Industrial Estate, Tobacco Products Industrial Estate, Analytical Hierarchy Process (AHP)